2020
DOI: 10.3390/microorganisms8020236
|View full text |Cite
|
Sign up to set email alerts
|

Community Structures and Antifungal Activity of Root-Associated Endophytic Actinobacteria in Healthy and Diseased Cucumber Plants and Streptomyces sp. HAAG3-15 as a Promising Biocontrol Agent

Abstract: Microorganisms related to plant roots are vital for plant growth and health and considered to be the second genome of the plant. When the plant is attacked by plant pathogens, the diversity and community structure of plant-associated microbes might be changed. The goal of this study is to characterize differences in root-associated endophytic actinobacterial community composition and antifungal activity between Fusarium wilt diseased and healthy cucumber and screen actinobacteria for potential biological contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…As endophytes have the functions of promoting plant growth, improving plant resistance, and helping plants resist pests and diseases (Table 2), the use of endophytes as a biological antagonist has great advantages in preventing and controlling plant diseases, and there are an increasing number of researches on the inhibition of plant diseases by endophytes worldwide. Cao et al 120 . showed that the number of endophytic actinobacteria in cucumber ( Cucumis sativus L.) infected with Fusarium wilt was more than that in the root of healthy cucumber, and the endophytic strain HAAG3‐15 isolated from the root had strong antifungal ability against Fusarium wilt and broad‐spectrum antifungal activity.…”
Section: Endophytesmentioning
confidence: 99%
“…As endophytes have the functions of promoting plant growth, improving plant resistance, and helping plants resist pests and diseases (Table 2), the use of endophytes as a biological antagonist has great advantages in preventing and controlling plant diseases, and there are an increasing number of researches on the inhibition of plant diseases by endophytes worldwide. Cao et al 120 . showed that the number of endophytic actinobacteria in cucumber ( Cucumis sativus L.) infected with Fusarium wilt was more than that in the root of healthy cucumber, and the endophytic strain HAAG3‐15 isolated from the root had strong antifungal ability against Fusarium wilt and broad‐spectrum antifungal activity.…”
Section: Endophytesmentioning
confidence: 99%
“…The maximum and minimum values of the fungal mycelium radius were measured in absence of or in presence of antagonists, respectively. The results were expressed as a percentage of the mycelium inhibition rate (IR %=A -B/A×100) where A was the maximum value of the mycelium radius and B was the minimum value [58,59].…”
Section: Antagonistic Effects Of Neau-ld23 T On Phytopathogenic Fungimentioning
confidence: 99%
“…Among the known antibiotics available on the market, more than 60% of them are produced by the genus Streptomyces [43]. Some of the antibiotics produced by the genus [44][45][46][47]. Similarly, the organophosphate secreted by S. albus CAI-21 may be used in biological control of M. phaseolina.…”
Section: Identification Of the Active Secondary Metabolite From S Almentioning
confidence: 99%